2015
DOI: 10.2147/dddt.s75221
|View full text |Cite
|
Sign up to set email alerts
|

Alisertib induces cell cycle arrest and autophagy and suppresses epithelial-to-mesenchymal transition involving PI3K/Akt/mTOR and sirtuin 1-mediated signaling pathways in human pancreatic cancer cells

Abstract: Pancreatic cancer is the most aggressive cancer worldwide with poor response to current therapeutics. Alisertib (ALS), a potent and selective Aurora kinase A inhibitor, exhibits potent anticancer effects in preclinical and clinical studies; however, the effect and underlying mechanism of ALS in the pancreatic cancer treatment remain elusive. This study aimed to examine the effects of ALS on cell growth, autophagy, and epithelial-to-mesenchymal transition (EMT) and to delineate the possible molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 67 publications
(92 reference statements)
1
11
0
Order By: Relevance
“…The relationship between mTOR signaling pathway and pancreatic cancer has been revealed by multiple recent publications [7375]. As a regulatory mechanism for cell proliferation, mTOR signaling pathway has been confirmed to have crosstalk with various core regulatory factors and their respective signaling pathways including MAPK , TP53 , RAS, and EGFR [7679]. Some of such regulatory factors have also been contained in our results.…”
Section: Resultssupporting
confidence: 70%
“…The relationship between mTOR signaling pathway and pancreatic cancer has been revealed by multiple recent publications [7375]. As a regulatory mechanism for cell proliferation, mTOR signaling pathway has been confirmed to have crosstalk with various core regulatory factors and their respective signaling pathways including MAPK , TP53 , RAS, and EGFR [7679]. Some of such regulatory factors have also been contained in our results.…”
Section: Resultssupporting
confidence: 70%
“…Autophagy pathways also provide a rescue mechanism by stabilizing the cell metabolism [ 22 ]. A connection between cell cycle or DNA damage and autophagy is discussed in literature, but not fully understood, yet [ 23 , 24 , 25 ]. Further in vivo experiments with Fv1 could include the combination with inhibitors of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…D'assoro et al showed that these features include the loss of the CD24 cell surface receptor, a mesenchimal morphology, a transcriptomic signature of 11 genes involved in EMT and metastases, together with the overexpression of the SMAD5 and SOX2 markers, which directly promote EMT and stemness. The AURKA inhibitor Alisertib was shown to block these features, arresting the cells at the G1/S checkpoint and inducing autophagy [123], and PARP-dependent apoptosis [119]. However, the molecular mechanism by which AURKA induces EMT remains to be fully disclosed.…”
Section: Interphase Aurka Is Involved In Cell Migration and Invasionmentioning
confidence: 99%